Identifying, studying and making good use of macromolecular crystals. Issue 8 (1st August 2014) - Calero, Guillermo; Cohen, Aina E.; Luft, Joseph R.; Newman, Janet; Snell, Edward H.
<x xml:space="preserve">Abstract</x> Structural biology has contributed tremendous knowledge to the understanding of life on the molecular scale. The Protein Data Bank, a depository of this structural knowledge, currently contains over 100 000 protein structures, with the majority stemming from X‐ray crystallography. As the name might suggest, crystallography requires crystals. As detectors become more sensitive and X‐ray sources more intense, the notion of a crystal is gradually changing from one large enough to embellish expensive jewellery to objects that have external dimensions of the order of the wavelength of visible light. Identifying these crystals is a prerequisite to their study. This paper discusses developments in identifying these crystals during crystallization screening and distinguishing them from other potential outcomes. The practical aspects of ensuring that once a crystal is identified it can then be positioned in the X‐ray beam for data collection are also addressed.